The Routledge reader of African American rhetoric
1 online resource (xxvi, 867 pages)
Keywords: The Routledge Reader of African American Rhetoric is a comprehensive compendium of primary texts that is designed for use by students, teachers, and scholars of rhetoric; and for the general public interested in the history of African American communication. The volume and its companion website include dialogues, creative works, essays, folklore, music, interviews, news stories, raps, videos, and speeches that are performed or written by African Americans. Both the book as a whole and the various selections in it speak directly to the artistic, cultural, economic, gendered, social, and political condition of African Americans from the enslavement period in America to the present, as well as to the Black Diaspora.